2012
DOI: 10.4102/curationis.v35i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of secondary school girls towards contraception in Limpopo Province

Abstract: Unplanned teenage pregnancy constitutes an important health problem, whilst contraceptive services are free throughout South Africa and the number of Termination of Pregnancy (TOP) services is increasing. The purpose of this study was to assess the knowledge, attitudes and practices of secondary school girls towards contraception in Thulamela Municipality of Limpopo Province, South Africa. A quantitative descriptive study design was used and respondents were selected by convenience sampling from a population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 17 publications
8
40
1
Order By: Relevance
“…This was in line with the findings of previous reports. [5,6,13] This finding was further supported by Ramathuba et al, [7] who reported that the adolescents who participated in their study could not discuss contraceptives with their parents or partners.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This was in line with the findings of previous reports. [5,6,13] This finding was further supported by Ramathuba et al, [7] who reported that the adolescents who participated in their study could not discuss contraceptives with their parents or partners.…”
Section: Discussionsupporting
confidence: 60%
“…Data relevant to the study's objectives and research questions were collected using a self-administered questionnaire. The questionnaire was developed based on various prior studies, [5][6][7] and it was divided into four sections, namely, Section (1), the sociodemographic characteristics of the participants; Section (2), an evaluation of their knowledge regarding contraceptive methods; Section (3), statements about the participants' awareness regarding contraception; and Section (4), their perceptions and behavior in relation to contraceptives. The pretesting of the questionnaire was performed with 15 students to ensure that the participants understood all the questions as well as to examine the reliability and validity of the scales used in our survey.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Some reasons may be described as determinant factors for this discontinuation, such as: the teenager does not like the side effects of the oral contraceptives, the unplanning sexual activities and the absence of receiving advice from the health team regarding the immediate postpartum. 2,5,14,15 The understanding of factors that contribute to teenage pregnancy and its repetition are fundamental to the development of adequate interventions. 16 As for this , and as a result of the RRP threaten the well-being and the future of adolescents due to physical, emotional and social risks which it entails, the objective of this study was to determine the prevalence of RRP and associated factors in adolescents attended at the Family Health Strategies (ESF) in the city of Caruaru-PE.…”
Section: Introductionmentioning
confidence: 99%
“…However, access to mainstream contraceptive methods is more limited in sub-Saharan Africa than elsewhere; on average contraceptive prevalence in Africa is approximately 27%, less than half the average throughout the world. 1 Emergency contraception (EC) is a method to prevent pregnancy after an unprotected act of sexual intercourse and before the potential time of implantation. 2 It is well established that many unintended pregnancies occur as a result of unprotected intercourse, inadequate contraceptive measures or failure of a method.…”
Section: Introductionmentioning
confidence: 99%